2014
DOI: 10.1534/genetics.113.157776
|View full text |Cite
|
Sign up to set email alerts
|

Robust Estimates of Divergence Times and Selection with a Poisson Random Field Model: A Case Study of Comparative Phylogeographic Data

Abstract: Mutation frequencies can be modeled as a Poisson random field (PRF) to estimate speciation times and the degree of selection on newly arisen mutations. This approach provides a quantitative theory for comparing intraspecific polymorphism with interspecific divergence in the presence of selection and can be used to estimate population genetic parameters. Although the original PRF model has been extended to more general biological settings to make statistical inference about selection and divergence among model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The answer is most likely to be in the limitations of the methods, e.g., number of populations that can be studied, differences in models of nucleotide evolution. Interestingly, a comparison between a Poisson random field (PRF) method and *BEAST divergence time estimates across the Isthmus of Panama for 22 bird sister pairs reported that *BEAST almost consistently estimated deeper divergence times [ 58 ]. The continued improvement of these and related methods will facilitate improved parameter estimates in the future [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The answer is most likely to be in the limitations of the methods, e.g., number of populations that can be studied, differences in models of nucleotide evolution. Interestingly, a comparison between a Poisson random field (PRF) method and *BEAST divergence time estimates across the Isthmus of Panama for 22 bird sister pairs reported that *BEAST almost consistently estimated deeper divergence times [ 58 ]. The continued improvement of these and related methods will facilitate improved parameter estimates in the future [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous sets of evolutionary lineages replace the original projections of reproductive isolation and evolutionary independence. Differences between sympatric, congeneric species in morphology and vocalizations, supplemented by DNA divergences, help us to calibrate new thresholds of species status (Isler et al 1998, Helbig et al 2002, Tobias et al 2010, Amei and Smith 2013. The revised classifications, which in the New World will resurrect the insights of Robert Ridgway and other giants on whose shoulders we stand, better reflect phylogeny and evolutionary status, more accurately define biodiversity, guide improved DNA sampling patterns of bird populations, and enable informed conservation management (Peterson 2006, De Queiroz 2007.…”
Section: The Polytypic Species Concept Revisitedmentioning
confidence: 99%
“…However, species may respond differentially to topography and climate. Comparative phylogeographic analyses have thus far been conducted on subsets of bird communities; studies from the Americas [17][18][19], Africa [12,20,21], Australia [22] and southeast Asia [2] exhibit varied patterns among the species sampled. Such studies include species pairs that are often picked to make specific, often extreme, comparisons like wet/ humid species versus dry [17,23].…”
Section: Introductionmentioning
confidence: 99%